2012
DOI: 10.1017/s1360674311000293
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting binomial order in English: ordering constraints and reversibility

Abstract: The factors governing word order in binomials, i.e. coordinated word pairs of the same word class, have been the subject of discussion for a long time in linguistics. For example, why do we say law and order but not order and law? The article tests seventeen different potential ordering constraints that have previously been suggested, from the areas of semantics, phonology and word frequency, by checking over 500 high-frequency binomials extracted from the BNC against them. A clear hierarchy of constraints is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 14 publications
4
47
0
Order By: Relevance
“…We then coded the NP conjuncts for a number of variables which have been suggested to influence their order, based on the psycholinguistic literature and the studies on irreversible binomials (see above). Taking into account variables from research on irreversible binomials seems justified, as it has been shown in previous research that those factors underlie order also in reversible cases (Mollin, 2012;Lohmann, 2014). As outlined above we are most interested in influences A. Lohmann, T. Takada / Lingua 152 (2014) 48--64 52 pertaining to either conceptual or lexical accessibility; however, other influences were also considered to obtain a maximally accurate model illustrating which factors underlie the internal order of conjuncts, and to control for potentially confounding influences.…”
Section: Data and Operationalization Of Variablesmentioning
confidence: 99%
“…We then coded the NP conjuncts for a number of variables which have been suggested to influence their order, based on the psycholinguistic literature and the studies on irreversible binomials (see above). Taking into account variables from research on irreversible binomials seems justified, as it has been shown in previous research that those factors underlie order also in reversible cases (Mollin, 2012;Lohmann, 2014). As outlined above we are most interested in influences A. Lohmann, T. Takada / Lingua 152 (2014) 48--64 52 pertaining to either conceptual or lexical accessibility; however, other influences were also considered to obtain a maximally accurate model illustrating which factors underlie the internal order of conjuncts, and to control for potentially confounding influences.…”
Section: Data and Operationalization Of Variablesmentioning
confidence: 99%
“…Besides guiding interpretation, word order also reveals specific meaning as convincingly shown by research on binomials (Hegarty, Watson, Fletcher, & McQueen, 2011;McGuire & McGuire, 1982;Mollin, 2012). Mollin's (2012) extensive corpus analyses show that many binomials have a predominant order (brother and sister, Spring and Summer) and that some are particularly unlikely to appear in reverse order.…”
Section: Word-order and Meaningmentioning
confidence: 83%
“…Mollin's (2012) extensive corpus analyses show that many binomials have a predominant order (brother and sister, Spring and Summer) and that some are particularly unlikely to appear in reverse order. Binomials with a strong canonical order and a low degree of reversibility show specific semantic constraints, such that the first term will be the more powerful and more agentic.…”
Section: Word-order and Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…The two exceptions are seminal but scantly noted work by McGuire and McGuire (1992), and work by Hegarty and colleagues reviewed below. Linguists and psycholinguists, in contrast, have extensively studied word order in conjoined phrases.Linguistic research has investigated word properties that are associated with initial position in a conjoined phrase and linked it to multiple word attributes concerning phonology, use frequency, and semantics (for reviews, see Lohmann, 2014;Mollin, 2012). While our focus is on semantic factors, we want to keep in mind that multiple interrelated factors are at play.…”
mentioning
confidence: 99%